Volunteering from altruism to otherness - Halba, Bénédicte (Traditiones (Ljubljana), 2014)
Volunteering is no longer a marginal phenomenon. It has become a crucial issue since the beginning of the 1990s, with studies implemented at both the European and global levels to measure volunteer population and also to give a theoretical background to volunteering. The concept of volunteering includes altruism, charity, and solidarity. It is the touchstone of civil society. Being a volunteer implies creating and developing both social capital and human capital. Volunteers acquire personal, social, and professional skills. Being a volunteer also means being an active citizen; it has a specific meaning with regard to migration. The concept of "otherness" may be more significant from this perspective.
Keywords: cultural anthropology; kulturna antropologija; prostovoljstvo; volunteering; prostovoljci; altruism; altruizem; solidarity; solidarnost; civil society; social work; socialno delo; civilna družba; državljanstvo